Determinant of Consumer Awareness Toward Halal Food During The Covid-19 Pandemic: Evidence from Indonesia - Muhammad Anwar Fathoni; Suryani Suryani; Sumilir Sumilir (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
This study aims to explain the level of consumer awareness of halal food products. In addition, this study also aims to examine the factors that determine the level of consumer awareness of halal food products. This research is explanatory research with a quantitative approach. Sources of data in this study are primary and secondary data. This study uses primary data sources with survey methods. The number of samples used was as many as 385 people. The data obtained were analyzed using Structural Equation Modeling (SEM) analysis. This study is a development of previous research that investigated and measured the index of consumer awareness of halal food products in Indonesia. This study found that the level of consumer awareness of halal food in Indonesia is very high. Meanwhile, the determining factors are religiosity, media exposure, and hygiene reasons.